Local Religious Authority and Peacebuilding: The Role of Religious Leaders in Preventing Electoral Violence in Indonesia and Beyond - Bahrudin, Memet Isa (Definisi: Jurnal Agama dan Sosial Humaniora, 2024)
This study aims to analyze the role of religious leaders in preventing electoral and political violence across different national contexts, and to examine how religious authority contributes to the construction of social peace. The study is grounded in the concepts of moral authority, social legitimacy, and religion as an instrument of peacebuilding within political life. It employs a qualitative approach through literature review and comparative analysis of case studies from Nigeria, Uganda, Indonesia, and Guyana, focusing on the interventions of religious leaders in electoral dynamics. The findings reveal that religious leaders play a significant role in mitigating political violence through peace messaging, social mobilization, and collaboration with state institutions and civil society. However, the study also identifies key challenges, including inconsistent engagement of religious actors and the risk of religious politicization, which may undermine their constructive role. The study recommends the institutional integration of religious leaders into conflict prevention policies and the strengthening of interfaith dialogue as a long-term strategy for cultivating a peaceful political culture. This study contributes to the discourse on religion and politics by positioning religious leaders as strategic actors in peacebuilding and by proposing a collaborative framework between the state and religious actors in preventing political violence.